(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Radiation therapy remains a cornerstone in the management of breast cancer; however, radiation-induced skin injuries (radiodermatitis) significantly affect patients’ quality of life and may interrupt treatment schedules. Despite advances in radiotherapy techniques, acute and chronic cutaneous toxicities remain prevalent. The present study evaluates the clinical effectiveness of innovative topical therapeutic agents, including hyaluronic acid-based formulations, corticosteroid creams, and herbal bioactive compounds, in the prevention and management of radiation-induced skin damage in breast cancer patients.